2009
DOI: 10.1258/ce.2009.009020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical ethics consultation in Europe: a comparative and ethical review of the role of patients

Abstract: Clinical ethics has developed significantly in Europe over the past 15 years and remains an evolving process. While sharing our experiences in different European settings, we were surprised to discover marked differences in our practice, especially regarding the position and role of patients. In this paper, we describe these differences, such as patient access to and participation or representation in ethics consults. We propose reasons to explain these differences, hypothesizing that they relate to the histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 17 publications
0
42
0
1
Order By: Relevance
“…A recent survey of clinical ethics committees in the UK showed the number of identified committees to have risen from 20 in 2001 to 82 in 2010 (Slowther, McClimans, and Price, 2012). Clinical ethics networks have also been established in Europe with the European Clinical Ethics Network (Fournier et al, 2009) and in the UK with the United Kingdom Clinical Ethics Network (UKCEN) in an attempt to embed clinical ethics as a core element of health care systems (Slowther, 2008).…”
Section: The Origins Of Ces Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey of clinical ethics committees in the UK showed the number of identified committees to have risen from 20 in 2001 to 82 in 2010 (Slowther, McClimans, and Price, 2012). Clinical ethics networks have also been established in Europe with the European Clinical Ethics Network (Fournier et al, 2009) and in the UK with the United Kingdom Clinical Ethics Network (UKCEN) in an attempt to embed clinical ethics as a core element of health care systems (Slowther, 2008).…”
Section: The Origins Of Ces Servicesmentioning
confidence: 99%
“…Some committees actively educate their members, while others do not or are unable to. Some services involve patients and families directly in their deliberative process and allow them to refer to the service, in many others support is primarily if not exclusively for clinicians (Fournier et al, 2009 Val et al (2001Val et al ( , 2004 and the Royal College of Physicians (2005) show ethics consultations are mostly requested for end-of-life issues, decisions about withdrawing "futile" treatments, and late-term abortions. Other frequently occurring issues include disagreement among clinicians, professional misconduct, and concerns related to truthtelling and confidentiality.…”
Section: Evaluation Of Ces Servicesmentioning
confidence: 99%
“…8 In Europe, there is similar interest and discussion about the potential role and outcomes of clinical ethics consultations. 23 In Australia, as in the UK, Clinical Ethics Committees are not mandated by government accreditation processes, although there is growing interest in their development. In 2000, McNeil 24 reported that there were roughly 120 Clinical Ethics Committees in operation, representing between 10 and 20% of hospitals surveyed.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] CES services are an established feature of healthcare in the US and Canada and are becoming so in the UK and elsewhere in Europe and Asia. [6][7][8][9][10][11][12][13][14][15][16][17][18] The growth of such services internationally is often taken to indicate a growing perceived need among clinicians for assistance with the many ethical and legal issues they face. [14][15][16][17] Although clinicians have always faced complex ethical decisions, the need for CES is driven by factors that have increased the ethical complexities of patient care, such as greater social and value plurality, technological advances and heightened patient autonomy.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18] The growth of such services internationally is often taken to indicate a growing perceived need among clinicians for assistance with the many ethical and legal issues they face. [14][15][16][17] Although clinicians have always faced complex ethical decisions, the need for CES is driven by factors that have increased the ethical complexities of patient care, such as greater social and value plurality, technological advances and heightened patient autonomy. [19][20][21] Clinicians have traditionally dealt with ethical issues by keeping their own counsel, turning to trusted colleagues or professional codes of ethics or seeking guidance from religious authorities.…”
Section: Introductionmentioning
confidence: 99%